PERAN KESADARAN MANUSIA DALAM KEAMANAN INFORMASI DAN SOCIAL ENGINEERING - Nugroho, Mahendra Adhi; Asih, Sri Wulan; Karunia, Anisah Novi (Gapenas Publisher, 2024)
Human understanding in managing information system security reflects efforts to protect computer and non-computer devices, facilities, data, and information from misuse by irresponsible parties. Information security aims to ensure the confidentiality, availability, and integrity of information resources in a company. Information system security involves day-to-day protection, referred to as information security, as well as operational preparation. This article aims to build a hypothesis regarding the influence between variables for subsequent research. This research uses qualitative methods with literature studies and is exploratory. The results of this literature review article show that (1) human awareness influences information system security, (2) information technology influences information system security, and (3) social engineering influences information system security